Quantitative Structure-Activity Relationships of the Trisubstitued Triazines Bearing Aminopyrimidine Group - Bi, Hui-Min; Hu, Jun-Ping; Chai, Xing-Quan; Li, Shu-Xian; Li, Qing; Dong, Chun-Hua (Asian Journal of Chemistry, 2013)
The quantum study of the trisubstitued triazines bearing aminopyrimidine group was calculated by Gaussian 03 program. The energies, main composition and proportion of the frontier orbitals and electron density were analyzed. The study found that there exists correlation between the antibacterial activity of the trisubstitued triazines bearing aminopyrimidine group and energy. It was found that the C(3) and C(4) atoms were the active sites. In order to get the regression equation, the correlation analysis was done between some characteristic parameters of the compound and the experiental parameters of antimicrobial activity and good parameters were selected for the linear regression. The result shows that the total energy of compound (Etot), molecular weight (M), hydrophobic parameter (log P) are the main influencing factors for the antibacterial activity of the compound and when the log P is in the 0 3.881 interval.